Analisis Pengaruh Atmosfer Cafe, Kualitas Produk, dan Kualitas Layanan terhadap Kepuasan Konsumen untuk Mendorong Minat Beli Ulang pada Cafe Coffee Q - kahlil gibran (Universitas Harapan Medan, 2019)
This study aims (1) To determine the influence of cafe atmosphere on customer satisfaction. (2) To know the effect of product quality to customer satisfaction. (3) To know the influence of service quality to customer satisfaction. (4) To find out the influence of cafe atmosphere on buying interest. (5) To know the effect of product quality on buying interest. (6) To know the effect of service quality on buying interest. (7) To know the effect of consumer satisfaction on the buying interest. The research approach used is quantitative approach. The population of this study is all consumer café coffee Q. The sample of this study amounted to 100 people determined by slovin method. Data analysis technique using path analysist, system using with application SPSS . The result of this research are: (1) Atmosphere of cafe has no significant effect to consumer satisfaction in cafes Q. (2) Product quality significantly influence consumer satisfaction at café coffee Q. (3) Quality of service is not have a significant effect on consumer satisfaction at cafe Q. (4) Cafe atmosphere has no significant effect on the interest to buy back at coffee cafe Q. Furthermore there is indirect influence of café atmosphere on the interest of buy back through customer satisfaction insignificantly. (5) The quality of the product has a significant effect on the interest of buy back on coffee cafe Q. Furthermore there is indirect effect of product quality on the interest of buy back through customer satisfaction insignificantly. (6) The quality of service has significant influence to the interest of buy back at coffee cafe Q. Furthermore there is indirect influence of service quality to the interest of buy back through customer satisfaction insignificantly. (7) Consumer satisfaction has no effect on the interest to buy back